2003
DOI: 10.1023/a:1022823605068
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Gluthathione (GSH) has been previously shown to promote the reduction of pentavalent antimony (Sb(V)) into the more toxic trivalent antimony (Sb(II)) in the antimonial drug, meglumine antimonate. However, this reaction occurred at acidic pH (pH 5) but not at the pH of the cytosol (pH 7.2) in which GSH is encountered. The aim of the present study was to further characterize the reaction between thiols and antimonial drugs, addressing the following aspects: (i) the reducing activity of cysteine (Cys) and cystein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(41 citation statements)
references
References 20 publications
0
41
0
Order By: Relevance
“…A marine macroalga, Sargassum sp., was the first reported organism able to reduce Sb(V) in seawater (59). In the treatment of leishmaniasis, several studies suggested that Sb(V), when used as a prodrug medicine, might be reduced in both the vertebrate host and the parasites (60)(61)(62)(63). However, the knowledge of bacterial Sb(V) reduction is limited.…”
Section: Microbial Antimony Cyclementioning
confidence: 99%
“…A marine macroalga, Sargassum sp., was the first reported organism able to reduce Sb(V) in seawater (59). In the treatment of leishmaniasis, several studies suggested that Sb(V), when used as a prodrug medicine, might be reduced in both the vertebrate host and the parasites (60)(61)(62)(63). However, the knowledge of bacterial Sb(V) reduction is limited.…”
Section: Microbial Antimony Cyclementioning
confidence: 99%
“…Abiotic Sb V reduction has been much less studied. It is well known that Sb V is reduced by thiol-containing ligands [96,97] and, for instance, cysteine is widely used as a Sb V pre-reductant in HG methods, but the extent of such reduction by thiol compounds in real environmental systems is unknown. Abiotic reduction of Sb V by green rust [98,99] and magnetite and mackinawite [100] have been described recently.…”
Section: Presence Of Thermodynamically Unstable Speciesmentioning
confidence: 99%
“…Berman et al (4) and Demicheli et al (5) proposed that this drug interferes with the bioenergetic process of Leishmania amastigotes, forming stable complexes with ribonucleosides, which interfere with the parasite's fatty acid ␤-oxidation and glycolysis, promoting the depletion of intracellular ATP levels. Another hypothesis suggests that Sb V acts as a prodrug that is transformed into the more toxic trivalent form (Sb III ) to exert its antileishmanial activity (6)(7)(8)(9). In fact, some studies indicate that Sb III production in vivo is responsible for both therapeutic activity and antimony toxicity (10)(11)(12).…”
mentioning
confidence: 99%